The Effect of Prophetic Leadership on Employee Work Motivation at The Islamic Higher Education - Yusuf, Mahmud (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine the positive and simultaneous influence between prophetic leadership and work motivation on employee performance. This study involved employees at the Faculty of Economics and Islamic Business UIN Antasari Banjarmasin. This study uses a pre-experimental one-shot case study research design. The data analyzed in this study were obtained from survey results distributed to respondents, with the validity and reliability of the instrument first being tested. The number of instruments distributed to respondents is 10 items, with the answer choices using a Likert scale. Based on the analysis results, it is shown that Prophetic Leadership has a significant effect on work motivation. Furthermore, the value of R. Square is 0.343, and 65.7% of employees' work motivation is influenced by other variables not examined in this study. This research has implications for the importance of leaders in giving great attention to their employees to produce optimal performance